Grade Point Average Inflation and Academic Feudalism: A Study of Power Relations in the World of Higher Education - OK Arwansyah; Muhammad Thariq; Agung Suharyanto; Roynanda Sinaga (Universitas Medan Area, 2025)
The phenomenon of GPA inflation in Indonesian higher education reflects a complex social issue, where academic grades often fail to represent intellectual capacity and instead emerge as products of power relations between lecturers and students. This paper analyzes how symbolic power within academic spaces cultivates a culture of compliance and strategic adaptation among students in pursuit of cum laude honors. Employing a theoretical-critical approach and Michel Foucault’s discourse analysis, the study reveals that academic assessment systems frequently function as instruments of power reproduction, reinforcing academic feudalism and suppressing critical expression. High GPAs, in this context, are often symbolic compromises rather than genuine intellectual achievements. The findings suggest that social structures in universities shape students into submissive, administratively efficient individuals with limited intellectual courage—ultimately undermining the emancipatory function of higher education. This paper calls for academic decolonization to establish egalitarian dialogue, transparent grading systems, and a redefinition of respect (adab) as a foundation for critical and ethical discourse in education.